(untitled) (Konferensiyalar | Conferences, 2024)
The activity of the higher education system is aimed at training qualified specialists and experts, based on the requirements in the field of professional activity of highly qualified specialists, ensuring active use of integrative sciences to find solutions to situations that arise in the professional process.